Transformasi Kesatuan Sekerja Dalam Pembangunan Negara - Eden, Dzulzalani (2015)
The force of globalization has changed the employment structure and this has impacted not only the industrial relations systems of many countries, but also the institutions in which they operate, including the mechanism of trade unions (Aidt & Tzannatos (2002). Traditionally, the crucial roles of trade union have been to achieve decent wages and working conditions for their members. However, as unions are faced with the intense effect of globalization, it is imminent to operate beyond this ‘bread and butter’ issues (Hayman, 1997). This is important to ensure trade unions are still relevant and be seen as agents of change rather than resistance. The trade union movements, particularly in Malaysia, have also been faced with this new development forcing it to realign its roles with the government aspiration to become a high income nation. This requires them to expand their roles beyond traditional functions, but to include educations, social and cultural programmes.